Pengaruh faktor kerentanan fisik dan sosial akibat erupsi gunung merapi terhadap ketercapaian sdgs dan irbi - Muhammad Reza Aristo; Dyah Rahmawati Hizbaron (Universitas Gadjah Mada, 2023)
The purpose of this study was to identify the influence of physical and social vulnerability factors due to the eruption of Mount Merapi in Yogyakarta. Furthermore, this study identifies the significance of physical and social vulnerability to the achievement of the SDGs in Yogyakarta. The achievement of SDGs number 11 is supported by indicators of the percentage of the number of dead or missing victims to the total number of disaster events, disaster risk index, regional resilience index, number of resilient villages/kelurahan that have been formed, integrated early warning system, and availability of contingency plans. The achievement of SDGs number 13 is further explained using a simple indicator, namely greenhouse gas emissions. In this case, the research contribution is expected to add an indicator explaining the achievement of SDGs number 13 in addition to climate change. This study uses IRBI (Indonesian Disaster Risk Index) data to indicate the achievement of disaster risk reduction in the research area. The achievement of the SDGs, which has increased every year, certainly has positive implications for handling vulnerable groups. The location of this research study is the District of Turi. Turi sub-district is important to be studied considering the current conditions and potential future exposure to the eruption of Mount Merapi. This study utilizes the Analytical Hierarchy Process (AHP) technique to determine the weight of the indicators used in vulnerability modeling. The research data were tested using statistical analysis of data normality, probabilistic Poison, and the two-way ANOVA effect test. The results showed that there was no influence of the variables of physical vulnerability and social vulnerability on the existing SDGs. The conclusion of the research on the effect of physical and social vulnerability factors on the eruption of Mount Merapi Volcano shows that there is no influence of the value of physical and social vulnerability in Turi District on the achievement of SDGs in the form of the DIY Disaster Risk Index